The Multicultural-Based Independent Learning Curriculum at SMPN 7 Mataram: Strategies to Improve Academic Achievement and Tolerance - Liza Azhari; Rani Ayu Ningtias; Bayu Segara Agung; Nurmaulida Fajrina; Eti Sulastri; Sawaludin (al-Afkar, Journal For Islamic Studies, 2026)
This research discusses the implementation of the multicultural-based Independent Learning Curriculum at SMPN 7 Mataram as a strategy to improve academic achievement and build students' tolerant character. Education in Indonesia faces challenges in developing a generation that is not only academically intelligent but also has strong character amidst diversity. The Merdeka Belajar curriculum provides freedom for teachers and schools to adapt learning materials and methods according to student needs, while the multicultural approach aims to instill values of tolerance and respect for differences. The research method used is descriptive qualitative with data collection through observation, interviews and documentation. The research results show that SMPN 7 Mataram integrates multicultural values in the curriculum through project-based learning, cooperative learning, and inquiry- based approaches. Apart from that, extracurricular activities and cultural programs also contribute to shaping student character. The implementation of this curriculum not only improves students' academic achievements but also shapes them into individuals who are tolerant and ready to contribute to a multicultural society. Thus, the multicultural-based Independent Learning Curriculum at SMPN 7 Mataram is expected to become an effective model in education that prioritizes diversity and inclusiveness.